Because You’re Worth It! The Medicalization and Moralization of Aesthetics in Aging Women - Pussetti, Chiara (2021)
In this article—based on the fieldwork I conducted in Lisbon (Portugal) between 2018 and 2021, employing in-depth ethnography and self-ethnography—I describe the experience of the medicalization and moralization of beauty in Portuguese women aged 45–65 years. I examine the ways in which practitioners inscribe their expert knowledge on their patients’ bodies, stigmatizing the marks of time and proposing medical treatments and surgeries to “repair” and “correct” them. Beauty and youth are symbolically constructed in medical discourse as visual markers of health, an adequate lifestyle, a strong character and good personal choices (such as not smoking, and a healthy diet and exercise habits). What beauty means within the discourse of anti-aging and therapeutic rejuvenation is increasingly connected to an ideal gender performance of normative, white, middle-class, heterosexual femininity that dismisses structural determinants. The fantasy of eternal youth, linked to a neoliberal ideology of limitless enhancement and individual responsibility, is firmly entrenched in moralizing definitions of aesthetics and gender norms. Finally, my article highlights the ways in which the women I interviewed do not always passively accept the discourse of the devaluation of the ageing body, defining femininity and ageing in their own terms by creating personal variants of the hegemonic normative discourses on beauty and successful ageing.